God doesn't live here anymore : decline and resilience in the Canadian Church - Wood Daly, Michael; Thiessen, Joel, 1981- (Eugene, Oregon : Cascade Books, 2023)
"The church in Canada is in trouble. Media reports suggest that nine thousand churches are likely to close over the next ten years. The United Church of Canada reports closing a congregation a week. The Anglican Church of Canada anticipates closing its last congregation by 2040, and the Roman Catholic Church, Canada's largest religious denomination, reports having closed one-fifth of the tradition's 2,500 congregations. God Doesn't Live Here Anymore traces the story of the church in Canada from its far off historical roots in biblical times, rise to dominance in medieval Europe, role in the colonization of Canada, strained relations with Canada's First Nations, twentieth-century prominence, and the church's dramatic decline and loss of influence entering the twenty-first century. Wood Daly pulls no punches in calling the church to accept responsibility for its own decline, while maintaining hope that resurrection is still possible. The church, as Canadians may know it, might disappear, but for Christians death has never been the end of the story." --
1 The house of God: biblical perspectives on places of faith -- 2 Expanding markets: growth of the Mediterranean church -- 3 Moving heaven and earth: dominance in Europe -- 4 Brave new world: the church invades Turtle Island -- 5 Steeplechase: the Canadian church in the Twentieth Century -- 6 Just a brick in the wall: declining attendance and shifting values -- 7 House for sale: a market update -- 8 No place like home: finding a way forward.
Includes bibliographical references (pages 201-218) and index.
Keywords: Church attendance -- Canada; Church history; Canada -- Church history; Canada; Church history